1989
DOI: 10.1288/00005537-198907000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The predictive efficacy of the müller maneuver in uvulopalatopharyngoplasty

Abstract: Flexible pharyngoscopy with the Müller maneuver has been proposed as a method for selection of uvulopalatopharyngoplasty candidates. In this prospective study, its predictive efficacy has been evaluated in 24 consecutive obstructive sleep apnea patients undergoing uvulopalatopharyngoplasty. FPMM enabled us to accurately predict the uvulopalatopharyngoplasty outcome in 12 of the 24 patients (50%). Although flexible pharyngoscopy with the Müller maneuver appears to be helpful in the selection of candidates for U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 9 publications
1
58
0
3
Order By: Relevance
“…Although Sher et al [22] affirmed this maneuver to be successful in predicting the outcome of UPPP with a success rate of 87%, Katsantonis et al [23] reported a 33% success rate, but that they were better at predicting the unsuccessful patients with a ratio of 77.7%. These studies are conflicting, but in our opinion, this method is not deemed unnecessary in the evaluation of OSA patients; we found that when OSA severity increases modified Müller’s maneuver scores increase in both the retropharyngeal and tongue-base regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sher et al [22] affirmed this maneuver to be successful in predicting the outcome of UPPP with a success rate of 87%, Katsantonis et al [23] reported a 33% success rate, but that they were better at predicting the unsuccessful patients with a ratio of 77.7%. These studies are conflicting, but in our opinion, this method is not deemed unnecessary in the evaluation of OSA patients; we found that when OSA severity increases modified Müller’s maneuver scores increase in both the retropharyngeal and tongue-base regions.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible endoscope is inserted through one of the nostrils, while the patient is first in the sitting and then in the supine position awake, and is directed into the pharyngeal airway. The segment of the airway evaluated for collapse is the epiglottis, tongue base and soft palate, and in addition displacement and movement of the anterior, posterior and lateral pharyngeal walls are evaluated [24]. …”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent fibreoptic nasendoscopy with Mü ller9s manoeuvre [7], rhinomanometry and computed tomography (CT) scanning of the upper airway.…”
Section: Methodsmentioning
confidence: 99%